Childhood adversity and late-life depression: moderated mediation model of stress and social support - Lee, Jin-kyung; Lee, Jinhee; Chung, Moo-Kwon; Park, Ji Young; Shin, Taeksoo; Lee, Kyoung-Joung; Lim, Hyo-Sang; Hwang, Sangwon; Urtnasan, Erdenebayar; Jo, Yongmie; Kim, Min-Hyuk (Frontiers in Psychiatry, 2023)
Background As life expectancy increases, understanding the mechanism for late-life depression and finding a crucial moderator becomes more important for mental health in older adults. Childhood adversity increases the risk of clinical depression even in old age. Based on the stress sensitivity theory and stress-buffering effects, stress would be a significant mediator, while social support can be a key moderator in the mediation pathways. However, few studies have tested this moderated mediation model with a sample of older adults. This study aims to reveal the association between childhood adversity and late-life depression in older adults, taking into consideration the effects of stress and social support. Methods This study used several path models to analyze the data from 622 elderly participants who were never diagnosed with clinical depression. Results We found that childhood adversity increases the odds ratio of depression by approximately 20% in older adults. Path model with mediation demonstrates that stress fully mediates the pathway from childhood adversity to late-life depression. Path model with moderated mediation also illustrates that social support significantly weakens the association between childhood adversity and perceived stress. Conclusion This study provides empirical evidence to reveal a more detailed mechanism for late-life depression. Specifically, this study identifies one crucial risk factor and one protective factor, stress and social support, respectively. This brings insight into prevention of late-life depression among those who have experienced childhood adversity.